Dual-stent thrombectomy for recanalization of cerebral embolism caused by infective endocarditis: a case report - Zhang, Haiqi; Chen, Jianfei; Chang, Wansheng; Lin, Feng; Yin, Jijun (Frontiers in Neurology, 2024)
MethodsIn this case report, we present an in-depth narrative of a patient who was subjected to mechanical thrombectomy (MT) for an obstruction in the main trunk and bifurcation of the left middle cerebral artery subsequent to Infective Endocarditis (IE). Initial intervention using a solitary-stent technique proved to be ineffective; thus, we shifted to a dual-stent strategy, which successfully recanalized the compromised blood vessel.ResultsThe dual-stent retriever method can be especially advantageous for treating persistent clots that occur at arterial bifurcations resisting the efforts of a single-stent retriever during the MT process.ConclusionDual-stent thrombectomy increases the likelihood of clot extraction due to its ability to encompass a larger area of the thrombus within the stent’s framework, potentially improving the clinical outcomes.